2007
DOI: 10.1348/000709906x128396
|View full text |Cite
|
Sign up to set email alerts
|

Predicting academic self‐handicapping in different age groups: The role of personal achievement goals and social goals

Abstract: There were no grade-level or gender differences as regards the use of self-handicapping. The correlations among the variables revealed that, when the whole sample was considered, self-handicapping was positively related to performance goal orientations and pleasing significant others and negatively to achievement in mathematics. The results of hierarchical regression analysis showed that, in upper elementary and junior high schools, the association between achievement in mathematics and self-handicapping was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
29

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 68 publications
2
54
0
29
Order By: Relevance
“…In addition, there is abundant room for further studies in which the DAG questions are rephrased in terms of specific school subjects and/or specific time frames as school year, semester or month. Finally, although research has shown that mastery goals buffer students against self-handicapping (Deppe & Harackiewicz, 1996;Leondari & Gonida, 2007;Ntoumanis, Thøgersen-Ntoumani, & Smith, 2009), our results suggest that performance approach goals may do so as well, which is a promising idea to test experimentally. …”
Section: Strengths and Limitations Of The Present Study And Suggestiomentioning
confidence: 66%
“…In addition, there is abundant room for further studies in which the DAG questions are rephrased in terms of specific school subjects and/or specific time frames as school year, semester or month. Finally, although research has shown that mastery goals buffer students against self-handicapping (Deppe & Harackiewicz, 1996;Leondari & Gonida, 2007;Ntoumanis, Thøgersen-Ntoumani, & Smith, 2009), our results suggest that performance approach goals may do so as well, which is a promising idea to test experimentally. …”
Section: Strengths and Limitations Of The Present Study And Suggestiomentioning
confidence: 66%
“…For example, Tao (2003) found that having a socially-oriented achievement motivation can be beneficial in terms of facilitating effort and hard work, but it can also lead to feelings of guilt and anxiety. Another study conducted by Leondari and Gonida (2007) among Greek students have indicated that pursuing social approval goals could lead to self-handicapping strategies. Clearly, more research is needed to understand the 'dark' side of social goals.…”
Section: Some Caveatsmentioning
confidence: 99%
“…Although it is frequently assumed that social goals are more salient in collectivist settings, research among Western participants have also indicated that Western students also endorse social goals, and that social goals also influence learning outcomes (e.g. Dowson & McInerney, 2001, 2003Leondari & Gonida, 2007;Nelson & DeBacker, 2008;Urdan, 1994;Urdan & Maehr, 1995). Clearly, more research is needed to examine the generalizability of the social goal construct across different cultural groups.…”
Section: Some Caveatsmentioning
confidence: 99%
“…It is defined as the action of delaying the performance of an activity (Ferrari & Tice, 2000;Lay, Knish, & Zanatta, 1992;Leondari & Gonida, 2007;Schraw et al, 2007). For example, students procrastinate when they study only the day before the test or perform an extensive assignment close to the deadline.…”
mentioning
confidence: 99%